The effectiveness of online learning using moodle in improving understanding of the equipment and completeness of electrical engineering drawings for vocational school students - Kartiazim Kartiazim; Samsul Hadi (Institut Agama Islam Negeri (IAIN) Bone, 2022)
This study aims to determine the effectiveness of-assisted online learning Moodle, the difference in effectiveness between-assisted online learning Moodle and WhatsApp Group, and a comparison of the effectiveness between-assisted online learning-assisted learning Moodle and WhatsApp Group in improving students' understanding of the equipment and completeness of electrical engineering drawings. This research is quantitative research with a quasi-experimental type using a design nonequivalent control group. The population in this study were all students of class X from SMK Negeri 2 Yogyakarta with competency in electrical power installation engineering expertise consisting of four classes. Classes X. TITL-1 and X. TITL-2 were determined as a random sample. Both classes were given instruments pre-test and post-test to measure students' understanding of the equipment and completeness of electrical engineering drawings. To test the effectiveness of online learning, the one sample t-test was used, the difference in effectiveness was used the paired sample t-test, and the comparison of effectiveness used the independent sample t-test. The results of this study indicate: (1)-assisted online learning is Moodle effective in improving students' understanding of equipment and electrical engineering drawings; (2) there is a difference in effectiveness between online learning assisted by Moodle and WhatsApp Group in improving students' understanding of the equipment and completeness of electrical engineering drawings; and (3)-assisted online learning is Moodle more effective than-assisted online learning WhatsApp Group in improving students' understanding of equipment and electrical engineering drawings.